A Hierarchy of Acceptable Changes for Audiences of Nostalgic Narrative Media Brands. Issue 3 (1st October 2020) - Burgess, Jacqueline; Jones, Christian
ABSTRACT: This research used the branding concepts of brand nostalgia and brand heritage to examine and understand the changes that audiences will accept to a narrative media brand, a term proposed by this research to help distinguish between different types of media brands with the aim of focusing and advancing media branding research into fictional media. Narrative media brands involve a continuing fictional narrative such as the Pokémon brand chosen for this research. The context was Reddit comments posted about three trailers for the ' I Choose You' movie before its 2017 release to celebrate 20 years of the franchise. 574 Reddit posts were downloaded and analyzed using Leximancer software and an adaptation of netnography. It was found that changes that respected the audiences' parasocial relationships with the characters, as well as their perceptions of the brand's heritage, were acceptable. However, changes that audiences believed would threaten and undermine these relationships and the brand's heritage were not. This is presented in a pyramid hierarchy to conceptualize and categorize the level of change deemed acceptable by audiences. This research extends media branding research beyond seminal concepts by applying the concepts of brand nostalgia and brand heritage to a narrative media brand. The hierarchy has practical applications for the writers, producers, and brand managers of narrative media brands.